Disinformasi dan Hoaks di Media Sosial: Tantangan Etika Hukum dan Media Sosial - Azzahra, Hajar Auliya; Wibowo, Fiana Suryaningtyas; Setyaningrum, Nadia Rizqa; Zakiyyati, Keysya Aurelia Putri; Kamal, Ubaidillah Rizqa (Peneliti.net, 2026)
The rise of social media in the digital era has transformed communication patterns in Indonesian society but also brought significant challenges, particularly the spread of fake news and disinformation. This study analyzes the ethical and legal challenges in addressing fake news on social media and evaluates the effectiveness of Indonesia’s positive law. Using a normative juridical method, the research examines relevant laws, literature, and legal cases. Findings reveal that fake news has broad impacts, such as public confusion, panic, loss of trust in authorities, data falsification, and threats to social, political, and economic stability. The Fear of Missing Out (FOMO) phenomenon on social media also contributes to harmful behaviors like spreading hoaxes, hate speech, and cyberbullying. While legal instruments such as the ITE Law, the Criminal Code, and Law No. 1 of 1946 provide sanctions, enforcement faces challenges including difficulties in proving criminal intent, perpetrator anonymity, and ambiguous legal interpretations. The study highlights the need for synergy among fair law enforcement, enhanced digital literacy, and ethical communication practices. A collaborative effort involving the government, digital platforms, educational institutions, and society is essential to counter the negative impacts of hoaxes and foster a healthier digital information environment.